Pengaruh Karakteristik Individu dan Self Efficacy terhadap Kinerja Pegawai Dinas Perhubungan Morowali Utara - Syamsidar Syamsudin; Yoberth Kornelius; Andi Indriani Ibrahim; Riski Islianty (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the influence of individual characteristics and self-efficacy on employee performance at the North Morowali Regency Regional Transportation Office. This type of research is a quantitative research that identifies independent variables, namely individual characteristics and self-efficacy, as well as dependent variables, namely employee performance. The research sample amounted to 54 people who were determined using the Slovin formula from a total population of 120 people, with the Simple Random Sampling technique. Data were collected through questionnaire deployment and analyzed using multiple linear regression. The results of the study show that: (1) individual characteristics (X₁) and self efficacy (X₂) simultaneously have a significant effect on employee performance; (2) individual characteristics partially have a positive and significant effect on employee performance; and (3) partial self-efficacy also has a positive and significant effect on employee performance. These findings confirm that the better the quality of individuals and the higher the self-confidence of employees, the more optimal the performance they produce in carrying out their duties within the North Morowali Regency Regional Transportation Office.